“Estudo fitoquímico e investigação das atividades antioxidante e leishmanicida de extratos de Baccharis dracunculifolia D.C. (Asteraceae)” - Resende, Dimas Oliveira (2009)
This work reports the phytochemical investigation of the Baccharis dracunculifolia roots and the evaluation of the antioxidant and antileishmanial activities of different extracts of this plant. The analyzed crude extracts showed in vitro antioxidant activities and the root extract was the most active. Regarding the in vitro antileishmanial activity against Leishmania amazonensis, the hexane and hydroalcoholic root extracts displayed the best antiparasitic activities. The phytochemical study of the n-hexane and dichloromethane root extracts, performed by different chromatographic techniques such as High Performance Liquid Chromatography (HPLC), afforded the isolation and the identification of the benzodihidrofuran dihidroeuparin and the triterpene Baccharis oxide. Additionally, Gas Chromatography-Mass Spectrometric (GC-MS) of the n hexane root extract allowed the identification the following compounds: β friedelanol, friedelin, baccharis oxide, octadecanal, heptadecanal e ethyl octadecanoate. The obtained results in this work showed that B. dracunculifolia, mainly its root and leave extracts, possess high potential as source of antioxidant and antileishmanial compounds. Key-words: Baccharis dracunculifolia; phytochemical study; antioxidant activity; antileishmanial activity; DPPH; Leishmania amazonensis.